A Companion to American Fiction 1780-1865. - Samuels, Shirley (Blackwell companions to literature and culture., 2007)
A Companion to American Fiction 1780-1865 presents current critical responses to the broad range of American fiction written from the earliest declarations of nationhood to secession and civil war. The volume features contributions from over 35 leading international critics and scholars, who offer a cultural and historical context that serves to illuminate the fiction. The Companion covers both less well-known writers, such as Lydia Maria Child and George Lippard, and canonical authors, such as Nathaniel Hawthorne, Herman Melville, and Harriet Beecher Stowe. Contributors demonstrate how these.